2019
DOI: 10.1149/2.0031913jes
|View full text |Cite
|
Sign up to set email alerts
|

Topology Optimization of Electrolyte-Electrode Interfaces of Solid Oxide Fuel Cells based on the Adjoint Method

Abstract: Topology optimization is conducted to find the optimal meso-scale structure for the electrolyte-anode interfaces of solid oxide fuel cells. In the present optimization method, the total reaction current in the anode is chosen as an objective function to be maximized. The adjoint method is applied to compute the sensitivity of the objective function with respect to the interface shape, which is considered as the design variable. A cylindrical pillar structure is used as an initial guess and is iteratively modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…ASR corr /ASR plan ¼ 0.63 (see Table 1) and is equally associated to the contributions of the electrolyte and the electrodes. Therefore, one can clearly conclude that the increase of area by corrugation has an equivalent positive impact in both the electrolyte and the electrodes, which indicates that all the dominating phenomena are directly proportional to the area as theorized by other studies [42][43][44] (the same behaviour, with small variations in absolute values is maintained in all the temperature range).…”
Section: Solid Oxide Cells Performance In Fuel Cell and Co-electrolysis Modessupporting
confidence: 72%
“…ASR corr /ASR plan ¼ 0.63 (see Table 1) and is equally associated to the contributions of the electrolyte and the electrodes. Therefore, one can clearly conclude that the increase of area by corrugation has an equivalent positive impact in both the electrolyte and the electrodes, which indicates that all the dominating phenomena are directly proportional to the area as theorized by other studies [42][43][44] (the same behaviour, with small variations in absolute values is maintained in all the temperature range).…”
Section: Solid Oxide Cells Performance In Fuel Cell and Co-electrolysis Modessupporting
confidence: 72%
“…The height of the optimal structure plays a critical role for the length of the triple phase boundary (TPB) determination. 39 The increase in the triple phase boundary is linked to the increase in the surface area of the cell. 40 For the purposes of this study, surface area was controlled and measured and will be used in its stead.…”
Section: Discussionmentioning
confidence: 99%
“…From the theoretical calculation, Junya et al found branches at the top side and complex wrinkle-like substructures at the bottom side can be an optimized geometry for the electrolyte/electrode interface. The height of the optimal structure plays a critical role for the length of triple phase boundary (TPB) determination (36) simulation method to optimize the pillar-based electrolyte structures and proposed that with sufficient percolation of each phase, increasing the width and height of pillars can both enhance the electrochemical performance. Increasing the numbers of the pillars can also reduce the ASR of the interface.…”
Section: Discussionmentioning
confidence: 99%